MULTIVITAMINOUS COMPLEXIS IN NEUROPEDIATRICS - S.V. Balkanskaya; L.M. Kuzenkova; V.M. Studenikin (Union of pediatricians of Russia, 2009)
Therapeutic effect of multivitaminous complexis has been assessed in the open controlled study included 50 patients with psychoneurological disorders, aged from 4 to 16 years for 28 days. No pharmacological therapy was conducted in group of a control which included 15 patients with same disorders. Utilising the computer testing systems, basic of parameters cognitive functions (CF) were analyzed before and after the course of therapy. Statistically relevant positive effect of the vitaminis on cognitive functions was demonstrated.Key words: multivitaminous complexis, children, treatment, psychoneurological disorders.